2020
DOI: 10.1111/ans.15720
|View full text |Cite
|
Sign up to set email alerts
|

Breast disease in Timor‐Leste

Abstract: Background: Surgically treatable conditions are well documented in high-income countries. There is a gap in epidemiological understanding of breast pathology in many developing countries, Timor-Leste among them. This study was conducted to determine the burden of breast disease and to inform public health measures to address early detection, diagnosis and management. Methods: A retrospective quantitative case-control study was conducted at Guido Valadares National Hospital in Dili. Patients were included if th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…This disease is often found in adolescent girls, and its incidence decreases in adulthood [2]. Age of the 2nd and 3rd decade is the most common occurrence of FAM cases [2,19]. This was proven in a study conducted by Vijayakhumar et al (2013) in India, where this study found 139 out of 210 total cases of FAM, mostly occurring at the age of 16-30 years.…”
Section: Literature Reviewmentioning
confidence: 86%
“…This disease is often found in adolescent girls, and its incidence decreases in adulthood [2]. Age of the 2nd and 3rd decade is the most common occurrence of FAM cases [2,19]. This was proven in a study conducted by Vijayakhumar et al (2013) in India, where this study found 139 out of 210 total cases of FAM, mostly occurring at the age of 16-30 years.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Sebanyak 188 orang (42,3% dari total sampel) memiliki kasus fibroadenoma. 6 Lokasi fibroadenoma paling banyak adalah unilateral (86%) dan sisanya adalah bilateral Ukuran yang dilaporkan paling banyak adalah Fibroadenoma besar, yang memiliki ukuran antara 1-3cm (58%). Fibroadenoma raksasa (giant fibroadenoma) biasanya ditemui selama kehamilan atau menyusui.…”
Section: Pendahuluanunclassified
“…7 Perempuan yang menderita fibroadenoma mammae dapat mengalami gangguan psikologis yang cukup besar, beban finansial, kehilangan pendapatan, dan komplikasi kesehatan lebih lanjut. 6,8 Etiologi dan patogenesis FAM masih belum jelas disebabkan banyak predisposisi yang komplek atau multifaktorial, tetapi penjelasan umum yang digunakan adalah kadar hormon, obesitas dan riwayat keluarga. Fibroadenoma mammae memungkinkan menjadi faktor risiko untuk kanker payudara yang invasif.…”
Section: Pendahuluanunclassified
“…Fordyce et al have documented the burden of breast disease presenting to the National Hospital in Dili, Timor Leste, reporting an alarming rate of malignancy in young women, and the need for a national registry to inform policy makers. 14 As the focus for development assistance shifts from service delivery to capacity building, educational activities are an increasing component of programmes in the region. Nataraja et al detail the results of 4 years of simulation education at Yangon Children's Hospital, Myanmar, utilizing affordable and reproducible models that could be adapted to almost any setting.…”
mentioning
confidence: 99%
“…Fordyce et al . have documented the burden of breast disease presenting to the National Hospital in Dili, Timor Leste, reporting an alarming rate of malignancy in young women, and the need for a national registry to inform policy makers 14 …”
mentioning
confidence: 99%